Audit committee characteristics and earnings management practices - Melinda Lydia Nelwan; Billy Ivan Tansuria (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study revisits the effectiveness of the audit committee independence and expertise in preventing earnings management practices.  Studies in other studies with relatively stricter regulations showed the audit committee independence was effective to prevent earnings management.  On the contrary, studies in Indonesia were arguably outdated and shorter in period.  This study was conducted on Indonesian listed-manufacturing companies from 2009 to 2015. It used two earnings management model such as Modified Jones Model and Performance-Adjusted Modified Jones Model. The results showed that audit committee independence is effective to prevent earnings management practices.  However, it was found that audit committee expertise did not affect earnings management practices.  The results are consistent for both earnings management models. Although majority of the audit members in Indonesian listed manufacturing companies are experts in accounting and finance, the existence of those expert members did not affect the companies to engage or not engage in earnings management practices.  However, the accounting and/or financial expertise does not determine the effectiveness of the audit committee’s monitoring role.